Blood transfusion is correlated with elevated adult all-cause mortality and cardiovascular mortality in the United States: NHANES 1999 to 2018 population-based matched propensity score study - shi, jie (2024)
Background and aims: The association of blood transfusion with an increase in medium- and short-term mortality in specific populations has been confirmed. However, the correlation between blood transfusion and long-term mortality in the general population remains unclear. This cohort study evaluated the correlation between blood transfusion and overall and cause-specific mortality in the general American adult population. Methods: The authors utilized 10 sets of 2-year cycle data (1999−2018) from the National Health and Nutrition Examination Survey on the outcomes of adults who did and did not receive blood transfusions. Propensity scorematching (1:1) was performed based on age, sex, race, education level, marital status, poverty-income ratio, arteriosclerotic cardiovascular disease, cancer, anemia, hypertension, and diabetes status. After controlling for demographic characteristics and clinical risk factors, Cox regression analysis was performed to evaluate the correlation between blood transfusion and all-cause and cause-specific mortality. Results: The study included 48,004 adult participants. The risk of all-cause mortality increased by 101% with blood transfusion, and the risk of cardiovascular mortality increased by 165%. After propensity score-matching, 6,116 pairs of cases were retained, and the risk of all-cause mortality increased by 84% with blood transfusion, and the risk of cardiovascular mortality increased by 137%. The sensitivity analysis results were robust. Conclusions: In the general American population, blood transfusion significantly impacts long-term all-cause and cardiovascular mortality and may be an unacknowledged risk factor for death. Thus, the effective management of blood transfusion in the general population may be beneficial.